Step characteristics during long jump approach: reliance and asymmetry considerations - Exell, T.; Theodoru, A.; Panoutsakopoulos, V. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study's aim was to investiqate step characteristic reliance and asymmetry durina the long jump approach. Spatiotemporal data of the approach run were collected in national and international athletic competitions of 10 males (age 26.2 ± 4.1 yrs, height 1.84 ± 0.06 m, mass 72.77 ± 3.23 kg. PB 7.96 ± 0.30 m) and 9 females (26.3 ± 2.19 yrs. 1.73 ± 0.05 m, 55.75 ± 379 kg, 6.68 ± 0.20 m). Only two males showed step length reliance and only during late approach. Gtcp frequency reliance was demonstrated during total, early and late approach, most prevalently during the later (7/10 male & 3/9 female). Four males and females displayed step length asymme try whilst three |nales and two Temales were asymmetrical for frequency. No athletes showed step velocity asymmetry. In conclusion, asymmetrical demands of take-off were not consistently reflected in step characteristics.